Design of Hybrid Schottky-Ohmic Gate in Normally-Off p-GaN Gate AlGaN/GaN HEMTs. (28th December 2021) - Tsai, Wen-Shiuan; Qin, Zhen-Wei; Hsin, Yue-Ming
Abstract : This study proposes three hybrid Schottky-ohmic gate structures for normally-off p-GaN gate AlGaN/GaN HEMTs. One has a Schottky-gate cover on the ohmic-gate and has part of the area contact to the p-GaN surface at the left and right sides of ohmic-gate (Structure A). The two others only have the Schottky-gate contact to the p-GaN surface at the left side (Structure B) or right side (Structure C) of the ohmic-gate. Different gate metal designs change the hole injection from p-GaN to GaN channel and show various gate leakages. The optimized contact length of Schottky-gate can suppress on-state gate leakage current over two orders of magnitude compared to conventional ohmic p-GaN gate HEMT. The improved on-state maximum drain current is over 60 mA mm −1 compared to Schottky p-GaN gate HEMT. Optimal performance in Structure B with Schottky-gate contact length ranges from 0.8 to 1.8 μ m in a 2 μ m gate geometry.